The downregulation of tight junction proteins and pIgR in the colonic epithelium causes the susceptibility of EpCAM+/− mice to colitis and gut microbiota dysbiosis - Nie, Ya; Lin, Ting; Yang, Yanhong; Liu, Wanwan; Hu, Qing; Chen, Guibin; Huang, Li; Wu, Huijuan; Kong, Cunjie; Lei, Zili; Guo, Jiao (Frontiers in Molecular Biosciences, 2024)
Background The genetic factors play important roles on the pathogenesis of inflammatory bowel disease (IBD). EpCAM is highly expressed in the intestinal epithelium. It is still unclear if the decrease or somatic mutation of EpCAM could cause IBD. Methods The WT and EpCAM+/− mice were administrated with DSS intermittently for nearly 8 weeks. The colon, liver and feces were harvested to check the morphological and histological changes, the expression of inflammatory genes and the gut microbiota via H&E staining, immunofluorescence, qPCR, western blot and 16S rDNA sequence assays. Results The DSS administration induced more serious inflammation in the colon of EpCAM+/− mice than WT mice. Compared to DSS-induced WT mice, the transcriptional levels of IL-6, F4/80, Ly6g, Ly6d and Igha were significantly higher in the colon of DSS-induced EpCAM+/− mice. The protein levels of MMP7 and MMP8 and the activation of JNK, ERK1/2 and p38 were significantly increased in the colon of DSS-induced EpCAM+/− mice. The protein levels of CLDN1, CLDN2, CLDN3, CLDN7, OCLD, ZO-1 and pIgR were significantly decreased in the colon of DSS-induced EpCAM+/− mice. The serum concentration of LPS was significantly higher in the DSS-induced EpCAM+/− mice which caused the acute inflammation in the liver of them. The expression of Pigr was significantly reduced in the liver of DSS-induced EpCAM+/− mice. The ratio of Firmicutes/Bacteroidetes at the phylum level was higher in the gut microbiota of EpCAM+/− mice than WT mice. Conclusion In conclusion, the heterozygous mutation of EpCAM increased the susceptibility to colitis, gut microbiota dysbiosis and liver injury.